2007
DOI: 10.1128/iai.01416-06
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus fumigatusDoes Not Require Fatty Acid Metabolism via Isocitrate Lyase for Development of Invasive Aspergillosis

Abstract: Aspergillus fumigatus is the most prevalent airborne filamentous fungus causing invasive aspergillosis in immunocompromised individuals. Only a limited number of determinants directly associated with virulence are known, and the metabolic requirements of the fungus to grow inside a host have not yet been investigated. Previous studies on pathogenic microorganisms, i.e., the bacterium Mycobacterium tuberculosis and the yeast Candida albicans, have revealed an essential role for isocitrate lyase in pathogenicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 26 publications
4
45
1
Order By: Relevance
“…Mutants of C. albicans with a defective isocitrate lyase also displayed a dramatic reduction in virulence (Lorenz and Fink, 2001), which confirms the important role of the glyoxylate cycle in virulence of several pathogenic microorganisms. In contrast, investigations on A. fumigatus have shown that isocitrate lyase mutants retained the same virulence as the wild-type (Schöbel et al, 2007). Therefore, it is unlikely that A. fumigatus strongly depends on lipids as carbon sources during invasive growth.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Mutants of C. albicans with a defective isocitrate lyase also displayed a dramatic reduction in virulence (Lorenz and Fink, 2001), which confirms the important role of the glyoxylate cycle in virulence of several pathogenic microorganisms. In contrast, investigations on A. fumigatus have shown that isocitrate lyase mutants retained the same virulence as the wild-type (Schöbel et al, 2007). Therefore, it is unlikely that A. fumigatus strongly depends on lipids as carbon sources during invasive growth.…”
Section: Introductionmentioning
confidence: 83%
“…Our study, therefore, demonstrates that utilization of carbon sources available in the human host can differ considerably for various pathogens. The main causative organism for development of invasive aspergillosis, A. fumigatus, is not dependent on the glyoxylate cycle (Schöbel et al, 2007) but, as shown here, requires the methylcitrate cycle and thus most likely the degradation of proteins for manifestation of the infection. Incomplete amino-acid degradation leads to the accumulation of toxic propionyl-CoA that causes self-poisoning of the fungal cell.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the glyoxylate cycle is absent in mammals and therefore represents a potential drug target. Whereas this pathway appears to be dispensable for A. fumigatus-induced invasive aspergillosis (26,28), it was found to be virulence associated in infections by other microbial pathogens such as Mycobacterium tuberculosis and the yeast Candida albicans (17,21). In these pathogens, enzymes of the glyoxylate pathway were shown to contribute to the persistence of the microbes in phagocytic immune cells, a function which remains elusive for dermatophytes.…”
Section: Discussionmentioning
confidence: 99%